Zjawisko pracy kobiet: znaczenia, dylematy i kontrowersje na przestrzeni wieków - Judzińska, Aneta (Kultura-Społeczeństwo-Edukacja, 2024)
The article has an overview character. Based on the analysis of the subject, the article’s primary purpose is to synthetically show the phenomenon of women’s work over the centuries and to critically reflect on the place of women in the professional space. The article reflects on the phenomenon of women’s work in terms of socio-cultural. The considerations are focused on the issue of women’s work from a historical perspective, the professional position of Polish women after 1945, and the accompanying paradoxes also about the contemporary labour market. In almost every era (including today), certain types of women’s work could be equated with a sense of overload, injustice or lack of satisfaction. On the other hand, however, as demonstrated in this article, women’s work can become a tool for emancipation, provided the right political, cultural and social conditions exist.